2007
DOI: 10.1017/s0008423907071156
|View full text |Cite
|
Sign up to set email alerts
|

Judicial Decision Making In the Supreme Court of Canada: Updating the Personal Attribute Model

Abstract: . This study seeks to add to the current understanding of the political nature of the Supreme Court of Canada. We analyze a data set consisting of all nonunanimous published Supreme Court decisions for the period 1949 to 2000. A prior study by Tate and Sittiwong (1989) suggested a model of judge attributes for the period 1949 to 1985. We build on that analysis by extending the time period to 2000, which allows the impact of gender also to be assessed. We find that since the Court gained substantial docket cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
3
24
0
2
Order By: Relevance
“…Studies of crucial mass theory in legislatures also suggest that it is largely in the realm of issues that are of immediate importance for women, that we would likely see the greatest policy impact of female representation (Norris and Lovenduski 2001). Similarly, in the context of civil liberties claims, female justices at the Supreme Court level are more likely to render liberal decisions and at the same time render conservative decisions in criminal cases, which also confirms the findings of previous studies (Songer and Johnson 2007, Ostberg and Wetstein 2008, Johnson 2008.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Studies of crucial mass theory in legislatures also suggest that it is largely in the realm of issues that are of immediate importance for women, that we would likely see the greatest policy impact of female representation (Norris and Lovenduski 2001). Similarly, in the context of civil liberties claims, female justices at the Supreme Court level are more likely to render liberal decisions and at the same time render conservative decisions in criminal cases, which also confirms the findings of previous studies (Songer and Johnson 2007, Ostberg and Wetstein 2008, Johnson 2008.…”
Section: Discussionsupporting
confidence: 82%
“…Notably, however, even after controlling for these strong regional and partisan effects, judge gender appears to affect the trends in judicial voting. As noted in previous studies (Songer and Johnson 2007;Songer 2008), female justices in Canada were substantially more likely than their brethren to support pro-prosecution outcomes. In contrast to gender studies of judicial voting in the US that either have found no differences in criminal cases between male or female judges or have found female judges more likely to support a pro-defendant position, female justices on the Supreme Court of Canada appear to manifest support for a communitarian perspective that stresses the need to protect the interest of the larger society to be free from criminal actions that tend to break down the bonds that hold the community together.…”
Section: The Base Model Of Gender Differencesupporting
confidence: 57%
See 2 more Smart Citations
“…votes of individual justices~see, for example, Ostberg and Wetstein, 2007;Songer and Johnson, 2007;Schubert, 1965;Segal and Spaeth, 1993Rohde and Spaeth, 1976;Robertson, 1998;Peck, 1969!. Instead, the debate~Kritzer et al,1998!…”
mentioning
confidence: 99%